The Da'wah Strategy of the Prosperous Justice Party in Instilling Islamic Political Values in South Jakarta - Hilmi Aziz; Pia Khoirotun Nisa (STAI Publisistik Thawalib Jakarta, 2025)
The practices of money politics, identity misuse, and political apathy reflect deviations from Islamic political values. Therefore, the Prosperous Justice Party implements a da'wah strategy in South Jakarta. This study aims to analyze the da'wah strategy of the Prosperous Justice Party in instilling Islamic political values and to identify the supporting and inhibiting factors in South Jakarta. This research uses a case study method with interviews, observation, and documentation to collect data. Data processing involves condensation, data presentation, and conclusion drawing, followed by triangulation and confirmability to ensure data validity. Findings: The da'wah strategy of the Prosperous Justice Party is implemented through free health check-up services, the sale of low-cost necessities, and the building of relationships with religious leaders, organizations, and Islamic institutions. Meanwhile, the Member Development Unit demonstrates a rational da'wah strategy through a structured, focused cadre system and learning process. Inhibiting factors of the da'wah strategy include limited operational funds, a community that tends to be pragmatic and opportunistic, and the spread of false information. Supporting factors include the ownership of their building, the active role of the Member Development Unit, and support from religious leaders, organizations, and Islamic institutions. Conclusion: The da'wah conducted by the Prosperous Justice Party employs sentimental, rational, and sensory strategies through social programs and institutional relations to instill Islamic political values in society.